2016
DOI: 10.1186/s12913-016-1376-8
|View full text |Cite
|
Sign up to set email alerts
|

Relay model for recruiting alcohol dependent patients in general hospitals - a single-blind pragmatic randomized trial

Abstract: BackgroundA large proportion of the Danish population consumes more than the officially recommended weekly amount of alcohol. Untreated alcohol use disorders lead to frequent contacts with the health care system and can be associated with considerable human and societal costs. However, only a small share of those with alcohol use disorders receives treatment. A referral model to ensure treatment for alcohol dependent patients after discharge is needed. This study evaluates the i) cost-effectiveness ii) efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…When it comes to detecting overconsumption of alcohol among patients, it has been suggested that nurses could play a key role, both because they have a basic knowledge of health and diseases and because they are usually the ones who have the most contact with the patients (Groves et al, 2010;Lock, 2004). At the moment, a randomised controlled trial (RCT) called the Relay Study (Schwarz et al, 2016) is being conducted on seven somatic wards at two Danish hospitals. The purpose of the study is to investigate whether it is more efficient and cost-effective to rely on hospital staff to talk to patients about alcohol use or to have staff from outpatient alcohol treatment institutions come to the hospital and carry out brief interventions with the patients while they are hospitalised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to detecting overconsumption of alcohol among patients, it has been suggested that nurses could play a key role, both because they have a basic knowledge of health and diseases and because they are usually the ones who have the most contact with the patients (Groves et al, 2010;Lock, 2004). At the moment, a randomised controlled trial (RCT) called the Relay Study (Schwarz et al, 2016) is being conducted on seven somatic wards at two Danish hospitals. The purpose of the study is to investigate whether it is more efficient and cost-effective to rely on hospital staff to talk to patients about alcohol use or to have staff from outpatient alcohol treatment institutions come to the hospital and carry out brief interventions with the patients while they are hospitalised.…”
mentioning
confidence: 99%
“…In the Relay Study, all inpatients (+18 years) are screened using the Alcohol Use Disorder Identification Test (AUDIT) (Babor, de la Fuente, Saunders, & Grant, 1989). If they score 8 or more in the test, they are ran- ed from the study (Schwarz et al, 2016).…”
mentioning
confidence: 99%
“…Our study population consist of patients aged 18-101 hospitalized at Odense University Hospital (OUH) in Denmark for at least 24 hours from January 2012 until June 2016. Data captured for this study is created by linking two sources, the Relay study [15][16][17] and EHRs from OUH.…”
Section: A Dataset Collectionmentioning
confidence: 99%
“…The protocol and description of the full Relay project have been published separately (Schwarz et al 2016). Inclusion criteria were: admitted to the hospital departments in Odense or Aabenraa during the inclusion period (October 2013-June 2016), above the age of 18, hospitalized for a minimum of 24 h, residing in the uptake area of the involved alcohol treatment clinics and willing to participate in the study.…”
Section: Samplementioning
confidence: 99%